The Contribution Made by the Employed Housewives Living at Agricultural and Non-agricultural Villages to Their Family Income (A Case Study Conducted at Beraban Village, Kediri District and Wongaya Gede Village, Penebel District, Tabanan Regency) - LESTARI, MADE WAHYU; SUSRUSA, KETUT BUDI; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
The Contribution Made by the Employed Housewives Living at Agricultural and Non-agricultural Villages to Their Family Income (A Case Study Conducted at Beraban Village, Kediri District and Wongaya Gede Village, Penebel District, Tabanan Regency) The faster economic growth leads to multiple effect and inspires different economic activities which can absorb and cause housewives to have access to job opportunities. However, the job opportunities available at the agricultural village are different from those available at the non-agricultural village. As a consequence, the contribution made by the housewives living at the agricultural village to the family income is different from that made by those living in the non-agricultural village. This current study was intended to (1) identify the extent to which the housewives living at the agricultural village and non-agricultural village can contribute to the family income; (2) what motivated the housewives to work; and (3) what obstructed the housewives in their employment. This present study was conducted from July to August 2017 at Beraban Village, Kediri District, and at Wongaya Gede Village, Penebel District. The samples were taken using the Multistage Random Sampling, and totaled 77. The data were analyzed using the quantitative descriptive analysis, different test, and descriptive qualitative analysis. The result of the study shows that (1) the contribution made by the housewives living at the non-agricultural village was smaller than that made by those living at the agricultural village; (2) spare time inspired most of the housewives living at the non-agricultural village to work; (3) the household chores such as looking after their houses, taking care of their children, and the family members who were sick, and so forth obstructed them in their employment. Therefore, it is suggested to the housewives both living at the agricultural village and non-agricultural village to collaborate with the related institutions as an attempt to improve their productivity and efficiency in organizing their time.